PWE-028 HALO radiofrequency ablation for high grade dysplasia and early mucosal neoplasia arising in Barrett's oesophagus: interim results form the UK HALO radiofrequency ablation registry. (28th May 2012) - Haidry, R J; Dunn, J; Banks, M; Gupta, A; Butt, M A; Smart, H; Bhandari, P; Smith, L-A; Willert, R; Fullarton, G; Di Pietro, M; Penman, I; et al.
Abstract : Introduction: Barrett's oesophagus (BE) is the pre-cursor to oesophageal adenocarcinmoa (OAC). High grade dysplasia (HGD) and early mucosal neoplasia in BE has historically been treated with surgery. Recently there is a shift towards minimally invasive endotherapy with endoscopic mucosal resection (EMR) and Radiofrequency ablation (RFA). Methods: Prospective registry from 14 UK centers to audit RFA outcomes in patients with HGD and early neoplasia in BE. Prior to RFA, any visible lesions were first removed by EMR. Patients then underwent RFA 3 monthly until all visible BE was ablated or cancer developed. Biopsies were taken at the end of this protocol. Results: 216 patients have completed protocol, mean age 68.6 years (40–90), 81% male. Mean time to protocol end 11.3 months (IQR 8–14.3), median 2 ablations and mean of 2.4 (2–6) during protocol with mean 1.4 circumferential ablations and 1.2 focal ablations performed during protocol. Mean length BE segment ablated is 5.8 cm (1–20). CR-HGD was achieved in 83% patients at protocol end biopsy. CR-D was 76% and CR-BE 50% at this point. CR-D was more likely in short segment BE (<5 cm) at protocol end (82% vs 54%, p<0.0001, Fisher's exact test). Patients who required EMR during RFA protocol were less likely to achieve CR-D than those who had RFA alone (52% vs 79%, p=0.002, fishers exact test). 3.7% patients progressed to invasive cancer at protocol end. Complications include one perforation and 1% incidence of superficial tears. 37 patients have at least 12 months or more follow-up after successful completion of protocol (range 12–42), median 16.2 months. Durability in these is excellent with 95% dysplasia free at most recent biopsy. Conclusion: This is the largest series to date of patients undergoing RFA from 14 UK centers. End of protocol CR-D is satisfactory at 76% and successful eradication appears to be durable. Patients with short segment BE are likely to respond better. Our data represent real life outcomes of integrating minimally invasive endotherapy into demanding endoscopy service commitments. Competing interests: None declared.